A bibliometric analysis of digital immersion technology research in tourism based on WoS database - Zeng, Qiongxian; Hu, Xiaowen (Economics & Management Review, 2024)
This study utilized CiteSpace software to analyze 216 English documents from the Web of Science database. The analysis included the number of publications and keywords. The findings showed a steady increase in the number of related literatures since 2010, with a significant acceleration after 2019 and a peak in 2023. The keyword analysis revealed a focus on Computer Science, Software Engineering, Electrical & Electronic Engineering, Public, Environmental & Occupational Health, Computer Science, Information Systems, and Hospital, Leisure, Sport & Tourism. Research hotspots included Virtual Reality, Augmented Reality, Virtual Tourism, Satisfaction, Destination Image, Behavioral Intentions, and Place Attachment. The study’s scope has been expanding since 2015, reaching a peak between 2018 and 2023. This study is crucial for understanding the impact of digital immersion technology on the tourism experience and provides valuable insights for guiding future research directions, despite some limitations.